Narrative Medicine in China: A Critical Reflection - Xia, Tiancheng; Wu, Yuanjing (Acta Bioethica, 2025)
In recent years, narrative medicine has become a hot topic in Chinese humanistic medicine and has gained considerable influence. It is believed that narrative medicine can provide a constructive approach to balancing biomedical and humanities sciences, but there are many anti-narrative factors in China’s culture and medical practice. It is controversial whether narrative medicine can improve medical diagnosis and the doctor-patient relationship in China, therefore, despite many researchers believing that narrative medicine is very suitable for China, some critical reflections are still needed, to avoid doctors and patients spending too much energy on narrative, which may lead to treatment opportunities missing or create new troubles.